Anti-aging organic silicon foaming material and preparation method thereof
By using polyarylethersulfone resin as a modifier in silicone foamed materials, the problem of material aging is solved, its high temperature resistance and mechanical properties are improved, and it is suitable for new energy vehicle battery applications.
Patent Information
- Application Number
- CN202411788479.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Silicone foamed materials are prone to aging due to oxygen diffusion and oxidation reactions in new energy vehicle batteries, resulting in a decrease in buffering capacity and affecting battery life.
Polyaryl ethersulfone resin is used as a modifier to design its molecular structure and dissolve it in DMF to participate in the cross-linking reaction of silicone foamed materials, thereby improving the material's aging resistance and mechanical strength.
It significantly improves the high temperature resistance, mechanical strength and elasticity of silicone foamed materials, extends the service life of the materials, and shows good application potential in new energy vehicle battery applications.
Smart Images

Figure BDA0005174711560000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of organic silicon foam materials, and in particular to an anti-aging organic silicon foam material and a preparation method thereof. Background Art
[0002] Silicone foam material, also called silicone rubber foam material, is a porous viscoelastic polymer material with the advantages of high and low temperature resistance, high flexibility, light weight, sound insulation, heat insulation, shock absorption, etc. It is widely used in aerospace, automobile manufacturing, new energy development, electronics, national defense and military industry, and daily life. Among them, in the application of new energy vehicles, silicone foam material is used to fill the space between the battery cell and the shell and between adjacent battery cells to buffer the expansion and contraction of the battery during charging and discharging. However, during the application of the battery, there are problems such as heat release, which easily promotes oxygen diffusion and accelerates the oxidation reaction of the material, thereby accelerating the deformation and aging of the silicone foam material, reducing its buffering capacity, and thus affecting the life of the battery. Summary of the invention
[0003] In order to improve the aging resistance of an organosilicon foam material, the present application provides an aging-resistant organosilicon foam material and a preparation method thereof.
[0004] In the first aspect, the present application provides an anti-aging organic silicon foam material, which adopts the following technical solution: An anti-aging organic silicon foam material comprises a component A and a component B, wherein the component A comprises the following raw materials in parts by weight: 8-12 parts by weight of low-viscosity vinyl silicone oil, 65-75 parts by weight of high-viscosity vinyl silicone oil, 15-25 parts by weight of hydroxy silicone oil, 0.8-1.2 parts by weight of filler, 0.08-0.15 parts by weight of platinum catalyst and 15-25 parts by weight of polyarylethersulfone solution; the polyarylethersulfone solution is obtained by adding DMF to polyarylethersulfone until the polyarylethersulfone is completely dissolved, and the molecular structure of the polyarylethersulfone contains double bonds; The B component comprises the following raw materials in parts by weight: 8-12 parts by weight of low-viscosity vinyl silicone oil, 85-95 parts by weight of high-viscosity vinyl silicone oil, 85-95 parts by weight of hydrogen-containing silicone oil, and 2-4 parts by weight of filler.
[0005] By adopting the above technical scheme, polyarylethersulfone resin generally refers to a class of high molecular polymers containing sulfone groups, arylene groups and ether bonds in the main chain. Among them, the sulfone groups and benzene ring groups contained in it make the polyarylether resin have excellent rigidity and hardness. At the same time, the diphenylsulfone groups composed of sulfone groups and benzene rings in its molecular chain can also increase its high temperature resistance and oxidation resistance. Therefore, polyarylethersulfone has the inherent characteristics of high rigidity and high heat resistance. In addition, polyarylethersulfone is a flame-retardant organic polymer, and even if it burns, the amount of smoke is very small. The inventors added polyaryletherketone to the silicone system to prepare the foaming material, which improved the aging resistance and mechanical strength of the material. However, the insolubility and excessive rigidity of polyaryletherketone resulted in the silicone material being too rigid, affecting its elasticity, which was not conducive to the application of the foaming material. Therefore, the inventors of the present application designed the molecular structure of polyarylethersulfone resin and designed a preparation method so that its molecules contained double bonds. Based on its insolubility, it was dissolved in DMF so that it participated in the cross-linking reaction of the silicone foaming material in a dissolved state, thereby realizing the modification of the silicone foaming material, improving the aging resistance and mechanical strength of the silicone foaming material while maintaining good elasticity.
[0006] As a preference: the preparation method of the polyarylethersulfone is as follows: Using sulfolane as solvent, xylene as dehydrating agent, and anhydrous potassium carbonate as catalyst, 4,4'-difluorodiphenyl sulfone, bisphenol containing double bonds, and HO-Ar-OH are refluxed at 160-180°C for 2-4 hours, and then the system is heated to 190-210°C and stirred for 6.5-10 hours to obtain polyarylethersulfone; The total molar amount of the bisphenol containing a double bond and HO-Ar-OH is the same as the molar amount of 4,4'-difluorodiphenyl sulfone.
[0007] By adopting the above technical solution, the phenolic hydroxyl group replaces the fluorine atom in the 4,4'-difluorodiphenyl sulfone molecule through a nucleophilic substitution reaction, thereby forming a polymer chain structure.
[0008] Preferably, the molar ratio of the double bond-containing bisphenol to the HO—Ar—OH is 1:4-6; more preferably, the molar ratio is 1:5.
[0009] By adopting the above technical solution, when the amount of double-bond bisphenol added increases, the compressive strength and tensile strength of the silicone foam material are improved, and the height deformation shows a trend of first decreasing and then increasing. It is speculated that the higher the amount of addition, the greater the cross-linking density inside the silicone foam material, thereby improving its mechanical strength; the increase in its cross-linking density is conducive to the fusion between the polyarylethersulfone and the system, which helps to reduce the height deformation of the silicone foam material; but its cross-linking density is too high, which makes the rigidity of the silicone foam material too high and the elasticity is reduced, resulting in an increase in its height deformation, which is not conducive to the application of cushioning materials. The applicant uses the prepared polyarylethersulfone in the silicone rubber system to participate in cross-linking, and maintains an unexpectedly lower height deformation within the above range.
[0010] Preferably, the HO-Ar-OH is one or more of bisphenol A, bisphenol Z, biphenol and bisphenol S.
[0011] By adopting the above technical solution, HO-Ar-OH can theoretically be selected from any one or several of the above ranges, but not all of them are tested in the examples of this application.
[0012] Preferably, the double bond-containing bisphenol is 2,2'-diallylbisphenol A.
[0013] By adopting the above technical solution, the molecular structure of 2,2'-diallyl bisphenol A contains two double bonds, which can increase its reactivity, improve the crosslinking density of the silicone foaming material, and improve the reaction compatibility between the polyarylethersulfone and the system.
[0014] Preferably, the filler is fumed silica.
[0015] By adopting the above technical solution, fumed silica can be better applied to this system as an excellent reinforcing filler.
[0016] Preferably, the surface of the fumed silica is modified simultaneously by a silane coupling agent containing a double bond and a silane coupling agent containing a phenyl group.
[0017] By adopting the above technical scheme, the fumed silica is modified by a silane coupling agent containing double bonds so that its surface has double bonds, which can not only participate in the cross-linking reaction of the silicone foam material, but also improve its dispersibility in the system; under the action of these two aspects, the mechanical strength of the silicone foam material is improved, and its distribution is uniform, so that the limiting oxygen index is improved to a certain extent.
[0018] The inventors found that when the fumed silica modified by a double-bond silane coupling agent and a phenyl-containing silane coupling agent and a double-bond polyarylethersulfone are added to the organosilicon to prepare the foaming material, unexpected excellent aging resistance and mechanical properties are obtained. This may be because the polyarylethersulfone participates in cross-linking to form a cross-linked network with benzene rings to improve high temperature aging resistance and strength, and the modified fumed silica participates in cross-linking to obtain a phenyl-containing linear segment, which has a high degree of freedom and is evenly dispersed in the system, and a certain amount of phenyl is filled in the phenyl-containing cross-linked network. The entanglement of the molecules is conducive to improving the tensile strength and the elasticity, so that the overall aging resistance, elasticity and mechanical properties of the material are improved by using the two components together.
[0019] Preferably, the double bond-containing silane coupling agent is one or more of vinyl trisbutyl ketone oxime silane, 7-octenyl trimethoxy silane, vinyl triethoxy silane, acryloxymethyl trimethoxy silane, γ-methacryloxypropyl trimethoxy silane and vinyl triisopropoxy silane; the phenyl-containing silane coupling agent is one or two of phenyl triethoxy silane and phenyl trimethoxy silane.
[0020] Preferably, the double bond-containing silane coupling agent is 7-octenyltrimethoxysilane, which is used to modify silicon dioxide to prepare a foaming material with better aging resistance. The linear phenyl-containing chain segments provided by 7-octenyltrimethoxysilane in the system are more conducive to filling the phenyl groups in the cross-linked network, thereby improving aging resistance.
[0021] In a second aspect, the present application provides a method for preparing an anti-aging organosilicon foam material, which adopts the following technical scheme: A method for preparing an anti-aging organosilicon foam material, which comprises the following steps: S1, stirring and mixing the low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, hydroxy silicone oil, filler, platinum catalyst and polyarylethersulfone solution in component A to obtain a mixture of component A; S2, stirring and mixing the low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, hydrogen-containing silicone oil and filler of component B to obtain a mixture of component B; S3. Add component A and component B in a mass ratio of (9-11):1, stir and mix at (-10) to 5°C to obtain a foaming rubber material, vulcanize and foam the foaming rubber material at a low temperature of 55-65°C, and then vulcanize it at a high temperature. The temperature vulcanization is divided into three gradients, and the target temperatures are set to 70-80°C, 100-110°C, and 130-140°C, respectively. Finally, vulcanize it at 135°C to obtain an anti-aging silicone foam material.
[0022] By adopting the above technical scheme, the preparation method of the present application is relatively conventional, does not require special processes or equipment improvements, has a high tolerance for process parameters, and the qualified rate of the products obtained is 95% or above, which is suitable for large-scale production.
[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. By designing the molecular structure of polyarylethersulfone resin and designing the preparation method, the molecule has double bonds, and based on its insolubility, it is dissolved in DMF, so that it participates in the cross-linking reaction of the silicone foam material in a dissolved state, so as to achieve its modification of the silicone foam material and greatly improve the high temperature resistance of the silicone foam material.
[0024] 2. The compressive strength of the organosilicon foam material prepared in the present application is moderate, the tensile strength is good, and at the same time, its aging resistance is excellent. Its height deformation is 2.5% or less, and the minimum can reach 1.0%, and its limiting oxygen index is 29.8% or more, and the maximum can reach 32.5%. The organosilicon foam material prepared in the present application has great application potential in the battery application of new energy vehicles. DETAILED DESCRIPTION
[0025] The present application is further described in detail below in conjunction with the specific contents.
[0026] raw material The raw materials used in the preparation examples and embodiments of the present application are all commercially available, among which the viscosity of the low-viscosity vinyl silicone oil is 350 mPa.s; the viscosity of the high-viscosity vinyl silicone oil is 25000 mPa.s; the viscosity of the hydroxy silicone oil is 1000 mPa.s; the fumed silica is purchased from Shanghai Yunhe Materials Co., Ltd.; and the platinum catalyst is purchased from Dongguan Zhongxin Silicone Materials Co., Ltd.
[0027] Preparation Example Preparation Example 1 A polyarylethersulfone solution, the preparation method of which is as follows: 0.12 mol of 4,4'-difluorodiphenyl sulfone, 2,2'-diallyl bisphenol A, biphenylene and 0.14 mol of anhydrous potassium carbonate were added to 150 g of cyclopentane sulfone, and then 100 g of xylene was added as a dehydrating agent and stirred until dissolved; then, a water separator was installed under a nitrogen atmosphere, the temperature was raised to 170°C, and the reaction was refluxed for 2.5 hours to perform a sufficient salt-forming reaction; then, the reaction system was heated to 200°C and stirred for 7 hours; the total molar amount of 2,2'-diallyl bisphenol A and biphenylene was 0.12 mol, and the molar ratio of 2,2'-diallyl bisphenol A to biphenylene was 1:6; After the reaction liquid drops below 50°C, add 200g of 50°C deionized water polymer to obtain a precipitate, wash it three times with ethanol and deionized water respectively, and then dry it to obtain polyarylethersulfone, and then add DMF to the polyarylethersulfone and stir until the polyarylethersulfone is just completely dissolved to obtain a polyarylethersulfone solution.
[0028] Preparation Example 2 A polyarylethersulfone solution, which is different from Preparation Example 1 in that the molar ratio of 2,2'-diallylbisphenol A to biphenyl diphenol is 1:5, and the remaining steps are the same as Preparation Example 1.
[0029] Preparation Example 3 A polyarylethersulfone solution, which is different from Preparation Example 1 in that the molar ratio of 2,2'-diallylbisphenol A to biphenyl diphenol is 1:4, and the remaining steps are the same as Preparation Example 1. Example
[0030] Example 1 An anti-aging organic silicon foam material comprises a component A and a component B, wherein the component A comprises 10 g of low-viscosity vinyl silicone oil, 70 g of high-viscosity vinyl silicone oil, 20 g of hydroxy silicone oil, 1 g of filler, 0.1 g of platinum catalyst and 20 g of polyarylethersulfone solution; the component B comprises 10 g of low-viscosity vinyl silicone oil, 90 g of high-viscosity vinyl silicone oil, 88 g of hydrogen-containing silicone oil and 3.5 g of filler; wherein the polyarylethersulfone solution is from Preparation Example 1; and the filler is fumed silica; The preparation method of the anti-aging silicone foam material is as follows: S1. Weigh each raw material according to the formula of component A, and then put low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, hydroxy silicone oil, filler, platinum catalyst and polyarylethersulfone solution into a non-intrusive material homogenizer at a speed of 1600 r / min for 200 s to obtain a mixed material of component A; S2. Weigh each raw material according to the formula of component B, then put low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, hydrogen-containing silicone oil and filler into a non-intrusive material homogenizer, mix at a speed of 1600 r / min for 150 s, and obtain a mixture of component B; S3. Put the mixed materials of component A and component B into a non-intrusive material homogenizer at a mass ratio of 10:1, mix for 120 seconds at 0°C and a rotation speed of 1800 r / min to obtain a foamed rubber material, transfer the foamed rubber material to a polytetrafluoroethylene mold, and vulcanize and foam at 60°C for 30 minutes, then vulcanize at high temperature. The temperature vulcanization is divided into three gradients, and the target temperatures are set to 75°C, 105°C, and 135°C, respectively. Stay at each target temperature point for 5 minutes, and finally vulcanize at 135°C for 1 hour to obtain an anti-aging silicone foam material.
[0031] Example 2 An anti-aging organic silicon foam material is different from Example 1 in that the polyarylethersulfone solution is from Preparation Example 2, and the remaining steps are the same as those of Example 1.
[0032] Example 3 An anti-aging organic silicon foam material is different from Example 1 in that the polyarylethersulfone solution is from Preparation Example 3, and the remaining steps are the same as those of Example 1.
[0033] Example 4 An anti-aging organosilicon foam material, which is different from Example 2 in that its fumed silica is modified fumed silica of equal mass, and the preparation method of the modified fumed silica is as follows: 1.5 g of fumed silica was added to 100 mL of ethanol-water solution, where the ethanol-water solution was a mixed solution of ethanol and water in a volume ratio of 1:1. After ultrasonic dispersion, 3 g of vinyltriethoxysilane was added. The temperature was raised to 70° C., stirred for reaction for 8 h, filtered, washed, and dried to obtain modified fumed silica.
[0034] Example 5 An anti-aging organosilicon foam material, which is different from Example 2 in that its fumed silica is modified fumed silica of equal mass, and the preparation method of the modified fumed silica is as follows: 1.5 g of fumed silica was added to 100 mL of ethanol-water solution, where the ethanol-water solution was a mixed solution of ethanol and water in a volume ratio of 1:1. After ultrasonic dispersion, 3 g of phenyltriethoxysilane was added. The temperature was raised to 70° C., stirred for reaction for 8 h, filtered, washed, and dried to obtain modified fumed silica.
[0035] Example 6 An anti-aging organosilicon foam material, which is different from Example 2 in that its fumed silica is modified fumed silica of equal mass, and the preparation method of the modified fumed silica is as follows: 1.5 g of fumed silica was added to 100 mL of ethanol-water solution, where the ethanol-water solution was a mixed solution of ethanol and water in a volume ratio of 1:1. After ultrasonic dispersion, 1.5 g of vinyl triethoxysilane and 1.5 g of phenyl triethoxysilane were added. The temperature was raised to 70° C., the reaction was stirred for 8 h, filtered, washed, and dried to obtain modified fumed silica.
[0036] Example 7 An anti-aging organosilicon foam material, which is different from Example 2 in that its fumed silica is modified fumed silica of equal mass, and the preparation method of the modified fumed silica is as follows: 1.5 g of fumed silica was added to 100 mL of ethanol-water solution, where the ethanol-water solution was a mixed solution of ethanol and water in a volume ratio of 1:1. After ultrasonic dispersion, 1.5 g of 7-octenyltrimethoxysilane and 1.5 g of phenyltriethoxysilane were added. The temperature was raised to 70° C., the reaction was stirred for 8 h, filtered, washed, and dried to obtain modified fumed silica.
[0037] Comparative Example Comparative Example 1 An anti-aging organic silicon foam material is different from Example 1 in that its polyarylethersulfone solution is replaced by high-viscosity vinyl silicone oil of equal mass, and the remaining steps are the same as Example 1.
[0038] Comparative Example 2 An anti-aging organosilicon foam material is different from Example 7 in that the polyarylethersulfone solution is replaced by an equal mass of modified fumed silica, and the remaining steps are the same as those of Example 7.
[0039] Comparative Example 3 An anti-aging organosilicon foam material is different from Example 7 in that the modified fumed silica is replaced by an equal mass of polyarylethersulfone solution, and the remaining steps are the same as those of Example 7.
[0040] Performance testing Detection method / test method Anti-aging organosilicon foam materials were prepared according to the preparation methods of Examples 1-7 and Comparative Examples 1-3, and then tested according to the following testing method. The test results are shown in Table 1.
[0041] Compression strength: tested according to the test method in GB / T1041-92; Tensile strength: tested according to the test method in GB / T528-2009, the sample is dumbbell-shaped, and the tensile rate is 100mm / min; Aging resistance: According to the experimental method in GB / T7759.1-2015, the foamed silicone material is first compressed using a compression permanent setter, and then the sample loaded with 50% strain is placed in a 150°C oven for accelerated aging test. The aging time is 10 days, and then the sample is released and restored at room temperature for 24 hours. The height deformation of the foamed silicone (C) is calculated, C = [(h0-h1) / (h0-Hs)] × 100%, where: h0 is the height of the sample before aging, h1 is the height of the sample after aging, and Hs is the height of the fixture limiter. The larger the C value, the worse the aging resistance of the foamed silicone. Limiting oxygen index: Tested according to the test method in GB / T2406.2-2009.
[0042] Table 1 Test results of Examples 1-7 and Comparative Examples 1-3 It can be seen from Examples 1-7 and Comparative Examples 1-3, as well as the test data in Table 2, that the organic silicon foam material prepared in the present application has moderate compressive strength and good tensile strength. At the same time, it has excellent aging resistance, and its height deformation is 2.0% or less, with a minimum of 1.1%, and its limiting oxygen index is 31.2% or more, with a maximum of 31.8%. The organic silicon foam material prepared in the present application has great application potential in battery applications for new energy vehicles.
[0043] Polyarylethersulfone resin generally refers to a class of high molecular polymers whose main chain contains groups such as sulfone groups, arylene groups and ether bonds. Among them, the sulfone groups and benzene ring groups contained in it make the polyarylether resin have excellent rigidity and hardness. At the same time, the diphenylsulfone groups composed of sulfone groups and benzene rings in its molecular chain can also increase its high temperature resistance and oxidation resistance. Therefore, polyarylethersulfone has the inherent characteristics of high rigidity and high heat resistance. In addition, polyarylethersulfone is a flame-retardant organic polymer, and even if it burns, the amount of smoke is very small. The inventors of the present application designed the molecular structure of polyarylethersulfone resin and designed a preparation method so that its molecules have double bonds, and based on its insolubility, it is dissolved in DMF, so that it participates in the cross-linking reaction of the organosilicon foam material in a dissolved state, so as to realize its modification of the organosilicon foam material and greatly improve the high temperature resistance of the organosilicon foam material. It can be seen from the test data of Example 1 and Comparative Example 1. Combined with the test data of Examples 2-3, it can be seen that when the amount of 2,2'-diallyl bisphenol A added during the preparation of polyarylethersulfone increases, the compressive strength and tensile strength of the silicone foam material are improved, and the height deformation shows a trend of first decreasing and then increasing. It is speculated that the higher the amount of addition, the greater the cross-linking density inside the silicone foam material, thereby improving its mechanical strength; the increase in its cross-linking density is conducive to the fusion between polyarylethersulfone and the system, and helps to reduce the height deformation of the silicone foam material; but if its cross-linking density is too large, the rigidity of the silicone foam material is too high, the elasticity is reduced, and its height deformation is increased, which is not conducive to the application of cushioning materials.
[0044] It can be seen from the test data of Example 2 and Example 4-5 that the tensile strength, compressive strength and aging resistance of the material are improved to a certain extent by modifying the fumed silica; it can be seen from the test data of Example 4-6 that the silane coupling agent containing double bonds and the silane coupling agent containing phenyl are used to modify the fumed silica, and the tensile strength, compressive strength and aging resistance are improved compared to the single modification. This may be due to the fact that the modified fumed silica can obtain a linear segment containing phenyl while participating in cross-linking, and it has a high degree of freedom in the system, is evenly dispersed, and a certain amount of phenyl is filled in the cross-linked network containing phenyl. The entanglement of molecules is conducive to improving tensile strength, and is conducive to the improvement of elasticity, thereby improving the overall aging resistance, elasticity and mechanical properties of the material by using the two components together. It can be seen from Example 6 and Example 7 that the linear phenyl-containing segment provided by 7-octenyltrimethoxysilane in the system is longer, which is more conducive to the filling of phenyl in the cross-linked network, improving the molecular entanglement effect, and improving the aging resistance and other properties.
[0045] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. An anti-aging silicone foam material, characterized in that: The invention comprises component A and component B, wherein component A comprises the following raw materials in parts by weight: 8-12 parts by weight of low-viscosity vinyl silicone oil, 65-75 parts by weight of high-viscosity vinyl silicone oil, 15-25 parts by weight of hydroxy silicone oil, 0.8-1.2 parts by weight of filler, 0.08-0.15 parts by weight of platinum catalyst and 15-25 parts by weight of polyarylethersulfone solution; the polyarylethersulfone solution is obtained by adding DMF to polyarylethersulfone until the polyarylethersulfone is completely dissolved, and the molecular structure of the polyarylethersulfone contains double bonds; The B component comprises the following raw materials in parts by weight: 8-12 parts by weight of low-viscosity vinyl silicone oil, 85-95 parts by weight of high-viscosity vinyl silicone oil, 85-95 parts by weight of hydrogen-containing silicone oil, and 2-4 parts by weight of filler.
2. The anti-aging organic silicon foam material according to claim 1, characterized in that: The preparation method of the polyarylethersulfone is as follows: Using sulfolane as solvent, xylene as dehydrating agent, and anhydrous potassium carbonate as catalyst, 4,4'-difluorodiphenyl sulfone, bisphenol containing double bonds, and HO-Ar-OH are refluxed at 160-180°C for 2-4 hours, and then the system is heated to 190-210°C and stirred for 6.5-10 hours to obtain polyarylethersulfone; The total molar amount of the bisphenol containing a double bond and HO-Ar-OH is the same as the molar amount of 4,4'-difluorodiphenyl sulfone.
3. The anti-aging organic silicon foam material according to claim 2, characterized in that: The molar ratio of the double bond-containing bisphenol to the HO—Ar—OH is 1:
5.
4. The anti-aging organic silicon foam material according to claim 2, characterized in that: The HO-Ar-OH is one or more of bisphenol A, bisphenol Z, biphenol and bisphenol S.
5. The anti-aging organic silicon foam material according to claim 2, characterized in that: The double bond-containing bisphenol is 2,2'-diallylbisphenol A.
6. The anti-aging organic silicon foam material according to claim 1, characterized in that: The filler is fumed silica.
7. The anti-aging organic silicon foam material according to claim 6, characterized in that: The surface of the fumed silica is modified simultaneously by a silane coupling agent containing a double bond and a silane coupling agent containing a phenyl group.
8. The anti-aging organic silicon foam material according to claim 7, characterized in that: The double bond-containing silane coupling agent is one or more of vinyl trisbutyl ketone oxime silane, 7-octenyl trimethoxy silane, vinyl triethoxy silane, acryloxymethyl trimethoxy silane, γ-methacryloxypropyl trimethoxy silane and vinyl triisopropoxy silane; the phenyl-containing silane coupling agent is one or two of phenyl triethoxy silane and phenyl trimethoxy silane.
9. A method for preparing the anti-aging organosilicon foam material according to any one of claims 1 to 8, characterized in that: It includes the following steps: S1, stirring and mixing the low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, hydroxy silicone oil, filler, platinum catalyst and polyarylethersulfone solution in component A to obtain a mixture of component A; S2, stirring and mixing the low-viscosity vinyl silicone oil, high-viscosity vinyl silicone oil, hydrogen-containing silicone oil and filler of component B to obtain a mixture of component B; S3. Add component A mixture and component B mixture in a mass ratio of (9-11):1, stir and mix at -10 to 5°C to obtain a foaming rubber material, vulcanize and foam the foaming rubber material at a low temperature of 55-65°C, and then vulcanize it at a high temperature. The temperature vulcanization is divided into three gradients, and the target temperatures are set to 70-80°C, 100-110°C, and 130-140°C, respectively. Finally, vulcanize it at 135°C to obtain an anti-aging silicone foam material.
Citation Information
Patent Citations
Epoxidized polyarylether sulfone and composition of epoxidized polyarylether sulfone and epoxy resin
CN117247544A
Flame-retardant foamed silica gel material and preparation method thereof
CN118240384A
Antibacterial foaming silica gel material and preparation method thereof
CN118359933A
Copolymers of poly(aryl ether sulfones) and polydimethylsiloxane
US20210380763A1